Association Between Fluid Administration and Hemoglobin Changes During Perioperative Kidney Transplantation - Arundina Sanyoto; I Gde Raka Widiana; Gede Wira Mahadita; Yenny Kandarini; Nyoman Paramita Ayu; I Gusti Ngurah Agung Tresna Erawan (Indonesian Journal of Kidney and Hypertension, 2024)
Background: Chronic Kidney Disease (CKD) is a leading cause of mortality worldwide, particularly in Indonesia, so it requires effective treatment options like kidney transplantation. Optimal fluid therapy during the perioperative period is important for stable hemodynamics and graft function. However, guidelines for fluid administration remain lacking. Objective: This study investigates the association between fluid therapy and changes in hemoglobin levels in patients undergoing renal transplantation. Methods: A retrospective observational cross-sectional study was conducted at RSUP Prof. DR. I.G.N.G. Ngoerah Denpasar from January 2016 to August 2024. Data were collected from medical records of patients who underwent kidney transplantation, excluding those with incomplete data. Key variables included daily fluid intake and hemoglobin levels. The coefficient of variance was calculated and continued with correlation analyses utilizing Pearson correlation and linear regression to assess relationships between fluid administration and hemoglobin changes. Results: Of 28 patients, 10 met inclusion criteria, consisting of 4 males and 6 females. Analysis showed a strong correlation between the variance of fluid intake and the variance of hemoglobin levels (R = 0.86; R² = 0.74; P < 0.001). Conclusion: This study demonstrates a significant relationship between post-operative variance of fluid administration and variance of hemoglobin levels following kidney transplantation. It may have an impact on the management of post-operative reduction in hemoglobin levels.